2023
DOI: 10.3389/fmicb.2023.1128271
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inoculation with active microorganisms derived from adult goats on growth performance, gut microbiota and serum metabolome in newborn lambs

Abstract: This study evaluated the effects of inoculation with adult goat ruminal fluid on growth, health, gut microbiota and serum metabolism in lambs during the first 15 days of life. Twenty four Youzhou dark newborn lambs were selected and randomly distributed across 3 treatments (n = 8/group): autoclaved goat milk inoculated with 20 mL sterilized normal saline (CON), autoclaved goat milk inoculated with 20 mL fresh ruminal fluid (RF) and autoclaved goat milk inoculated with 20 mL autoclaved ruminal fluid (ARF). Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 79 publications
3
8
0
Order By: Relevance
“…In the present work, a trend of weight recovery was observed in the SRS group, which indicated that ruminal solid activity microorganisms are with the capacity to improve the growth of newborn lambs. Moreover, weight loss was also observed in our study similar to previous studies . The reason might be that newborn lambs are under neonatal stress after being removed from the dam.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In the present work, a trend of weight recovery was observed in the SRS group, which indicated that ruminal solid activity microorganisms are with the capacity to improve the growth of newborn lambs. Moreover, weight loss was also observed in our study similar to previous studies . The reason might be that newborn lambs are under neonatal stress after being removed from the dam.…”
Section: Discussionsupporting
confidence: 91%
“…We previously reported that ruminal fluid inoculated with active microorganisms enhanced growth performance, health condition, and overall metabolism partly through regulating the gut microbial community in newborn lambs. 21 This was in agreement with earlier studies that ruminal fluid inoculation accelerates rumen development, fermentation, and microbial colonization, which could serve as a strategy to smooth the transition from milk to solid feed and favor the animal performance. 22−24 In fact, few studies have discussed the developmental and healthy effects of ruminal solid microbiota transplantation during the first 15 days since birth.…”
Section: Introductionsupporting
confidence: 92%
See 3 more Smart Citations